Development of a process to change teachers’ misconceptions in using portfolio for elementary school student assessment - Tangdhanakanond, Kamonwan; Archwamety, Teara (Kasetsart Journal of Social Sciences, 2021)
The purposes of the present research were to develop a process to chang teachers’ misconceptions in using portfolio for elementary school student assessment, and to examine its effectiveness. Participants were divided into two subgroups, i.e., (1) the experimental group of 20 elementary school teachers who participated in the developed process, and (2) the control group of 20 elementary school teachers who did not. Research instruments were a questionnaire and a manual for changing teachers’ misconceptions. Data were analyzed by using mean and standard deviation, and t-test. Results were as follows: (1) The developed process to change teachers’ misconceptions consisted of four main steps, i.e., (1.1) self-analysis, (1.2) identification of the differences between the reasonable concepts and the pre-existing concepts, (1.3) understanding of the reasonable concepts, and (1.4) changing the misconceptions. Based on the experts’ opinion, the quality of the components in the developed process was in a high to highest level. (2) Overall, teacherscore on the concept of using portfolio after the participation in the developed process was statistically higher than that before the participation at the .01 level. Teachers who participated in the developed process had significantly higher score on the concept of using portfolio than those who did not participate at the .01 level.